Does eradication of Helicobacter pylori infection reduce hypergastrinema during long term therapy with proton pump inhibitors? - Ahmet K. GÜRBÜZ; Yaşar KÜÇÜKKARDALI; Yusuf YAZGAN; Melih ÖZEL; Taner POLAT (Turkish Journal of Gastroenterology, 2019)
-